3D-environment and muscle contraction regulate the heterogeneity of myonuclei - Rosa Nicolas; Marie-Ange Bonnin; Cédrine Blavet; Joana Esteves de Lima; Cécile Legallais; Delphine Duprez (Skeletal Muscle)
Abstract Skeletal muscle formation involves tight interactions between muscle cells and associated connective tissue fibroblasts. Every muscle displays the same type of organisation, they are innervated in the middle and attached at both extremities to tendons. Myonuclei are heterogeneous along myotubes and regionalised according to these middle and tip domains. During development, as soon as myotubes are formed, myonuclei at muscle tips facing developing tendons display their own molecular program. In addition to molecular heterogeneity, a subset of tip myonuclei has a fibroblastic origin different to the classical somitic origin, highlighting a cellular heterogeneity of myonuclei in foetal myotubes. To gain insights on the functional relevance of myonucleus heterogeneity during limb development, we used 2D culture and co-culture systems to dissociate autonomous processes (occurring in 2D-cultures) from 3D-environment of tissue development. We also assessed the role of muscle contraction in myonucleus heterogeneity in paralysed limb muscles. The regionalisation of cellular heterogeneity was not observed in 2D cell culture systems and paralyzed muscles. The molecular signature of MTJ myonuclei was lost in a dish and paralysed muscles indicating a requirement of 3D-enviroment and muscle contraction for MTJ formation. Tip genes that maintain a regionalized expression at myotube tips in cultures are linked to sarcomeres. The behaviour of regionalized markers in cultured myotubes and paralyzed muscles allows us to speculate whether the genes intervene in myogenesis, myotube attachment or MTJ formation.